Anomalous Origin of the Right Coronary Artery From the Pulmonary Artery and Mitral Regurgitation in a Newborn - Villavicencio, Rafael E.; Forbes, Thomas; Walters, Henry L.; Farooki, Zia Q. (Puerto Rico Health Sciences Journal, 2013)
See manuscript